Transcriptomic Analyses Reveal Increased Expression of Dioxygenases, Monooxygenases, and Other Metabolizing Enzymes Involved in Anthracene Degradation in the Marine Alga Ulva Lactuca - Moenne-Munoz, A; Gutierrez-Cutino, M; Gutierrez-Cutino, M; Santander-Meyer, R; Gonzalez-Figueroa, A (Frontiers Media S.A., 2022)
To analyze the mechanisms involved in anthracene (ANT) degradation in the marine alga Ulva lactuca, total RNA was obtained from the alga cultivated without ANT and with 5 μM of ANT for 24 h, and transcriptomic analyses were performed. A de novo transcriptome was assembled, transcripts differentially expressed were selected, and those overexpressed were identified. Overexpressed transcripts potentially involved in ANT degradation were: one aromatic ring dioxygenase, three 2-oxoglutarate Fe (II) dioxygenases (2-OGDOs), and three dienelactone hydrolases that may account for anthraquinone, phthalic anhydride, salicylic acid, and phthalic acid production (pathway 1). In addition, two flavin adenine dinucleotide (FAD)-dependent monooxygenases, four cytP450 monooxygenases, two epoxide hydrolase, one hydroxyphenylpyruvic acid dioxygenase (HPPDO), and two homogentisic acid dioxygenases (HGDOs) were identified that may also participate in ANT degradation (pathway 2). Moreover, an alkane monooxygenase (alkB), two alcohol dehydrogenases, and three aldehyde dehydrogenases were identified, which may participate in linear hydrocarbon degradation (pathway 3). Furthermore, the level of transcripts encoding some of mentioned enzymes were quantified by qRT-PCR are in the alga cultivated with 5 μM of ANT for 0–48 h, and those more increased were 2-OGDO, HGDO, and alkB monooxygenase. Thus, at least three pathways for ANT and linear hydrocarbons degradation may be existed in U. lactuca. In addition, ANT metabolites were analyzed by gas chromatography and mass spectrometry (GC–MS), allowing the identification of anthraquinone, phthalic anhydride, salicylic acid, and phthalic acid, thus validating the pathway 1. Copyright © 2022 González, Osorio, Romero, Méndez, Sepúlveda, Laporte, Gutierrez-Cutiño, Santander, Castro-Nallar and Moenne.